2010
DOI: 10.1111/j.1365-2672.2009.04544.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of membrane proteins regulating antimicrobial peptide resistance inVibrio parahaemolyticus

Abstract: Aims:  To identify proteins regulating antimicrobial peptide (AMP) resistance in Vibrio parahaemolyticus using membrane subproteome analysis. Methods and Results:  Three synthetic AMPs (Q4, Q6 and H1) and a natural one from fish (pleurocidin) were used for selection of AMP‐resistant strains. Differential expression patterns of the outer and inner membrane proteins (OMPs and IMPs) among wild‐type and the resistant strains were obtained using two‐dimensional gel electrophoresis. Two OMPs (TolC and flagellin) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…Dihydrolipoamide dehydrogenase provides acetyl-CoA required for TCA cycle and biosynthesis of fatty acids. High levels of dihydrolipoamide dehydrogenase was also reported in several other microorganisms like antimicrobial peptide-resistant Vibrio parahaemolyticus [46], toluene-resistant Pseudomonas putida [47] and tellurite- resistant E. coli [48]; suggesting the need of the enzyme for addition energy requirement in survival.…”
Section: Resultsmentioning
confidence: 81%
“…Dihydrolipoamide dehydrogenase provides acetyl-CoA required for TCA cycle and biosynthesis of fatty acids. High levels of dihydrolipoamide dehydrogenase was also reported in several other microorganisms like antimicrobial peptide-resistant Vibrio parahaemolyticus [46], toluene-resistant Pseudomonas putida [47] and tellurite- resistant E. coli [48]; suggesting the need of the enzyme for addition energy requirement in survival.…”
Section: Resultsmentioning
confidence: 81%
“…Indeed, several studies have reported that flagellin appeared on 2‐DE gels when bacterial membranes were isolated by ultracentrifugation and dissolved in SLS (Xu et al. 2004; Shen et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, peptidomic approaches tackle the study of resistance mechanisms, in support of the development of more sustainable antimicrobial agents (Shen et al 2010). For example, proteins regulating AMP resistance in Vibrio parahaemolyticus have been discovered using membrane subproteome analysis (Shen et al 2010).…”
Section: Peptidomicsmentioning
confidence: 99%
“…For example, proteins regulating AMP resistance in Vibrio parahaemolyticus have been discovered using membrane subproteome analysis (Shen et al 2010). …”
Section: Peptidomicsmentioning
confidence: 99%